Combined Periodontal, Orthodontic, and Prosthetic Treatment in an Adult Patient - Claudio Vinicius Sabatoski; Regis Claret Bueno; Ariel Adriano Reyes Pacheco; Matheus Melo Pithon; Orlando Motohiro Tanaka (Hindawi Limited, 2015)
A 41-year-old man had a significant loss of bone and supporting tissues with pathologic migration of several teeth and several missing teeth. He was treated with an interdisciplinary therapeutic protocol that included nonsurgical periodontal therapy based on strict control of supragingival plaque, subgingival periodontal therapy, orthodontic and endodontic treatment, and replacement of restorations. The orthodontic therapy was performed in a severely reduced bone support and the presence of pathological tooth migration after periodontal disease control. The interdisciplinary treatment protocol was the key to achieve a significant improvement in his facial and dental esthetics, masticatory function, and quality of life.